Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1021/jp4102042
|View full text |Cite
|
Sign up to set email alerts
|

Biamphiphilic Ionic Liquid Induced Folding Alterations in the Structure of Bovine Serum Albumin in Aqueous Medium

Abstract: 3-Methyl-1-octylimidazolium dodecylsulfate, [C8mim][C12OSO3], a vesicle forming biamphiphilic ionic liquid (BAIL) (J. Phys. Chem. B 2012, 116, 14363-14374), has been found to induce significant folding alterations in the structure of bovine serum albumin (BSA) in the aqueous medium at pH 7.0. Such alterations have been investigated in detail using various physicochemical and spectroscopic techniques. Different concentration regimes (monomeric, shared aggregation, and post-vesicular) of [C8mim][C12OSO3]-BSA int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
72
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 41 publications
8
72
4
Order By: Relevance
“…The smaller increase in D h from ≈ 8.0 nm to ≈ 11.0 nm in case of BSA-ILS-1 system is assigned to the monomeric interaction of ILS with BSA via electrostatic and hydrophobic interactions leading to partial unfolding of its secondary structure forming ILS-1-MCs. Such marginal increase in D h due to unfolding in monomeric concentration regime has also been reported for other imidazolium based ILSs bearing simple alkyl chain as well as for conventional surfactants 18,33,34. However, in case of BSA-ILS-2 and BSA-ILS-3 systems, a substantial increase in D h from ≈8 nm to 126 nm, and to ≈207 nm, respectively via intermediate structures having D h ≈40 nm up to C 1 is observed.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…The smaller increase in D h from ≈ 8.0 nm to ≈ 11.0 nm in case of BSA-ILS-1 system is assigned to the monomeric interaction of ILS with BSA via electrostatic and hydrophobic interactions leading to partial unfolding of its secondary structure forming ILS-1-MCs. Such marginal increase in D h due to unfolding in monomeric concentration regime has also been reported for other imidazolium based ILSs bearing simple alkyl chain as well as for conventional surfactants 18,33,34. However, in case of BSA-ILS-2 and BSA-ILS-3 systems, a substantial increase in D h from ≈8 nm to 126 nm, and to ≈207 nm, respectively via intermediate structures having D h ≈40 nm up to C 1 is observed.…”
supporting
confidence: 71%
“…From Figure S2B (supporting information), it has been found that N for different ILSs is 57 (ILS-1), 76 (ILS- based ILSs. 33,34 The increase in hydrophobic interactions between alkyl chains of ILSs forming hemi-micelles lead to decrease in interactions between BSA and ILSs stabilizing the ACs between C 2 and C 3 . This destabilizes the ACs leading to structural changes.…”
Section: Results Andmentioning
confidence: 99%
See 1 more Smart Citation
“…BSA has 19 Tyr residues in different domains and two Trp residues, namely Trp 134, present at the protein surface in domain I, and Trp 213, present in the hydrophobic binding pocket of the protein in domain II, that act as intrinsic fluorophores [58,59]. At the excitation wavelength of 280 nm, the quenching in BSA mainly occurs from binding of the surfactant ion in the vicinity of the forementioned Trp residues [60].…”
Section: Fluorescence Emission and Uv-vis Absorption Spectramentioning
confidence: 99%
“…BSA shows a strong fluorescence emission peak at 340 nm whose intensity gradually decreases upon addition of increasing surfactant concentrations, being accompanied by a blue shift of the maximum emission wavelength from 340 nm to 333 nm. The Trp 134 present at the surface of the protein in domain I is surrounded by a number of negatively charged aspartic (Asp) and glutamic (Glu) acid residues to which the cationic gemini (C 12 Cys) 2 can bind by electrostatic interactions thus perturbing the native conformation of BSA [60]. The observed changes suggest a shift of the fluorophores to a more hydrophobic environment that can be attributed to internalization of the fluorophore towards the protein hydrophobic core due to protein refolding (which is possible when protein gets stabilized [59,61]) or to hydrophobic interactions between the dodecyl chains of (C 12 Cys) 2 and hydrophobic amino acid residues around Trp 134, such as leucine (Leu), Tyr and Phe [60], leading to a decrease in intrinsic fluorescence intensity [26,28,57,62,63].…”
Section: Fluorescence Emission and Uv-vis Absorption Spectramentioning
confidence: 99%